Livestock water productivity - integrated approaches to crops and livestock and integrated policies - International Livestock Research Institute (International Livestock Research Institute, 2009)
Speaking at the December 2009 SLP meeting in Addis Ababa, Tilahun Amede (ILRI/IWMI) argues that livestock, although both a major source of livelihoods and user of water, are overlooked in policy-making on water productivity. This IWMI/ILRI research project in Ethiopia and Zimbabwe aims to understand the dynamics - and the strategies - that can improve water and livestock productivity, while minimizing land degradation. He shares three lessons emerging: First, that we need to improve the integration of crop and livestock; second, we meed to move policies from sectoral to integrated ones; and third, we need to ensure that the many useful technologies that exist actually reach the farmers.